2009
DOI: 10.1021/cg8006684
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Adsorption Sites of Protein Impurities and Their Effects on Step Advancement of Protein Crystals

Abstract: ABSTRACT:We measured noninvasively step velocities of elementary two-dimensional (2D) islands on {110} faces of tetragonal lysozyme crystals, under various supersaturations, by laser confocal microscopy combined with differential interference contrast microscopy. We studied the correlation between the effects of protein impurities on the growth of elementary steps and their adsorption sites on a crystal surface, using three kinds of proteins: fluorescent-labeled lysozyme (F-lysozyme), covalently bonded dimers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
62
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 55 publications
1
62
0
Order By: Relevance
“…In virtually all cases, these effects are strongly supersaturation dependent. The predominant interpretation is that the crystal undergoes a self-purifying transition by moving from an impurity-saturated state at low supersaturation toward an effective state of impurity repulsion at high driving forces (42,43). This can be understood by realizing that the impurity surface concentration at a given supersaturation depends on the ratio of the characteristic time of impurity adsorption and the exposure time of the impurity binding sites on the surface (44).…”
Section: Resultsmentioning
confidence: 99%
“…In virtually all cases, these effects are strongly supersaturation dependent. The predominant interpretation is that the crystal undergoes a self-purifying transition by moving from an impurity-saturated state at low supersaturation toward an effective state of impurity repulsion at high driving forces (42,43). This can be understood by realizing that the impurity surface concentration at a given supersaturation depends on the ratio of the characteristic time of impurity adsorption and the exposure time of the impurity binding sites on the surface (44).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously directly visualized elementary steps of protein crystals (>several nm in height) in aqueous protein solutions (∼1% reflectivity) with a sufficient contrast level by this technique (34)(35)(36)(37). Using LCM-DIM, we could also visualize dislocations in protein crystals during growth (38).…”
mentioning
confidence: 99%
“…Van Dreassche et al also revealed the relation between adsorption sites of impurities and their effects on step advancement by TIRF microscopy. 10 To our knowledge, we performed the first direct visualization of the attachment/detachment processes of fluorescent-labeled HEWL (F-HEWL) molecules on a relatively large interface (50 × 50 μm 2 ) between a tetragonal HEWL crystal (several hundred micrometers in thickness) and an equilibrium HEWL solution. 11 We revealed an induction period (∼70 min) after which the number density of F-HEWL molecules adsorbed mainly on steps increased linearly with the adsorption time.…”
Section: Introductionmentioning
confidence: 99%